Environmental Analysis of Massive Mask Waste due to the Covid-19 Pandemic in Indonesia - Rahmad Agus Dwianto; Tulus Haryono; Rianto (Institute of Medico-legal Publications Pvt Ltd, 2022)
The Covid-19 pandemic has a big impact. The requirement to use masks to prevent the spread of the virus increases the amount of mask waste. This study aims to analyze the environment due to the accumulation of mask waste during the Covid-19 pandemic in Indonesia. This research uses the literature study method from various literature references and qualitative analysis. Medical waste that is not managed with proper procedures has the potential to transmit the virus to other people. In addition, the pile of mask waste is also bad for the environment. Various appropriate designs and technologies are made for more appropriate and environmentally friendly management of mask waste.